2020
DOI: 10.1007/s12237-020-00783-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ferrous Iron and Hydrogen Sulfide on Nitrate Reduction in the Sediments of an Estuary Experiencing Hypoxia

Abstract: Hypoxia is common feature of eutrophic estuaries and semi-enclosed seas globally. One of the key factors driving hypoxia is nitrogen pollution. To gain more insight into the effects of hypoxia on estuarine nitrogen cycling, we measured potential nitrate reduction rates at different salinities and levels of hypoxia in a eutrophic temperate microtidal estuary, the Neuse River Estuary, North Carolina, USA. We also tested the effect of hydrogen sulfide and ferrous iron additions on the nitrate reduction pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Our finding of plant microbiome genes associated with nitrification, nitrate reduction and denitrification was consistent with evidence for extensive colonization of the sandy soils by aerenchymatous Equisetum rhizomes, as such sites are unlikely to experience extended periods of hypoxia known to inhibit nitrification and reduce denitrification ( Jäntti et al , 2021 ). Our study also detected genes such as hdrA , sox , dsr and soe associated with S oxidation or other S metabolism pathways ( Watanabe et al , 2014 , 2017 , 2019 ), though our observations suggested that S oxidation and S reduction may be performed by different bacteria at the two sites.…”
Section: Discussionsupporting
confidence: 86%
“…Our finding of plant microbiome genes associated with nitrification, nitrate reduction and denitrification was consistent with evidence for extensive colonization of the sandy soils by aerenchymatous Equisetum rhizomes, as such sites are unlikely to experience extended periods of hypoxia known to inhibit nitrification and reduce denitrification ( Jäntti et al , 2021 ). Our study also detected genes such as hdrA , sox , dsr and soe associated with S oxidation or other S metabolism pathways ( Watanabe et al , 2014 , 2017 , 2019 ), though our observations suggested that S oxidation and S reduction may be performed by different bacteria at the two sites.…”
Section: Discussionsupporting
confidence: 86%
“…Jantti et al. (2021) reported that soil denitrification capacity was almost completely lost and DNRA dominated in estuarine soils when hypoxia lasted for several months. Additionally, differences in hydrologic variation directly influence microbial community composition, with less variable conditions being preferred by DNRA and sulfate reducing bacteria (Chen et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies attributed this ammonium‐N accumulation to ammonification and suppression of nitrification (e.g., Doussan et al., 1998; Duval & Hill, 2007), whereas more recent studies increasingly attribute it to dissimilatory nitrate reduction to ammonium (DNRA; Chen et al., 2022; Covatti & Grischek, 2021; Liang et al., 2020; Murphy et al., 2020; Pandey et al., 2020; Su et al., 2022; Wang et al., 2020; G. Yin et al., 2017; Zhao et al., 2021). Stagnant and/or poorly mixed hydrologic conditions or flow paths with long residence time coupled with very low redox potentials and higher concentrations of electron donors such as organic carbon, dissolved iron (Fe), and sulfide have especially been shown to favor DNRA over denitrification (Burgin & Hamilton, 2007; Covatti & Grischek, 2021; Jantti et al., 2021; Reverey et al., 2018; Robertson & Thamdrup, 2017; Rutting et al., 2011; Sgourdis et al., 2011; Wang et al., 2020; G. Yin et al., 2017). Denitrification typically occurs for low organic C to nitrate‐N ratios (OC limiting) while DNRA has been reported for high organic C to nitrate‐N ratios (nitrate‐N limiting; >10–15; Chen et al., 2022; Pandey et al., 2020; Wei et al., 2022; S. Yin et al., 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both analyzes were optimized for 1 ml sample volumes. The 15 N 2 , 15 N 2 O, and 15 NH 4 + were analyzed as per Jäntti et al (2021; described in detail in Supplement 1).…”
Section: Incubation Experimentsmentioning
confidence: 99%